1559 Background noise in an Emergency Department: an observational study from staff and patient perspectives. Issue 12 (22nd November 2022) - Coats, Timothy; Emar, Murad; Smith, Ella
Abstract : Aims, Objectives and Background: Noise is a contributing factor to miscommunication, which may be exacerbated by wearing personal protective equipment. There has been little research on noise in the Emergency Department (ED). We aimed to (1) identify the noise levels experienced by staff and patients in different areas of an emergency department over the 24-hour cycle, (2) examine the impact of cubicle doors on the background noise experienced by the patient, and (3) assess the impact of monitor alarms on staff and patient noise levels. Method and Design: Using a standardised protocol, an observational study monitoring of staff and patient experience of noise was carried out in 3 areas of the ED (a resuscitation room, an area of patient cubicles with solid doors and an area of patient cubicles with curtains). The overall distributions of noise levels in each area were described and circadian variation plotted. The proportion of time that background noise was above key cutoff values known to impair communication was calculated (45dB and 65dB). Non-parametric methods were used to compare: (1) a patient cubicle with curtains compared to a solid door, (2) having the door open or closed, and (3) staff and patient exposure a monitor alarm. Results and Conclusion: In a large urban teaching hospitalEmergency Department noise was greater than 45dB for staff between 76% and 96% of the time (30% to 100% for patients). There was little difference across the 24hr cycle. A door decreased the noise experienced by patients, but only if left closed. In the resuscitation rooms monitor alarms were much louder for patients than for staff. Noise levels likely to impair communication are present in the ED for most of the time. Staff awareness and improved design of both buildings and equipment might mitigate this negative acoustic environment.